К проблеме литовско-белорусских лексических связей - Чекман, Валерий Николаевич (Baltistica, 1972)
ON THE PROBLEM OF LITHUANIAN-BYELORUSSIAN LEXICAL CONTACTSThis paper deals with some translation loans in Byelorussian from Lithuanian, namely, ten semantic loans (the type of blr. адбіты “enclosed, fenced”